Similarities and Differences of Neuropsychological Profiles in Children and Adolescents with Anorexia Nervosa and Healthy Controls Using Cluster and Discriminant Function Analyses. (24th November 2016) - Rose, Mark; Stedal, Kristin; Reville, Marie-Claire; van Noort, Betteke Maria; Kappel, Viola; Frampton, Ian; Watkins, Beth; Lask, Bryan
Abstract: Objective: This study aimed to identify discrete neuropsychological profiles and their relationship to clinical symptoms in 253 female children and adolescents with anorexia nervosa (AN) and 170 healthy controls (HCs) using a standardised neuropsychological assessment battery. Method: Hierarchical cluster analysis was used to identify the optimum number of clusters, and participants were assigned using K -means cluster analysis. Confirmatory discriminant function analysis determined which combination of neuropsychological variables best distinguished the clusters Results: Three distinct clusters in the AN sample emerged- AN cluster 1 (19%) - "neuropsychologically low average to average"; AN cluster 2 (33%) - "verbal/visuo-spatial discrepancy"; and AN cluster 3 (48%) - "verbally strong and neuropsychologically average to high average". Two distinct clusters in HCs were identified. HC cluster 1 (48%) demonstrated poor visuo-spatial memory scores and high verbal fluency scores, whilst HC cluster 2 (52%) scored within the average range on all neuropsychological tasks. Neuropsychological performance was associated with clinical symptoms of body mass index centile, Eating Disorder Examination subscale and global score, anxiety, depression and obsessions, and compulsions between the AN and HC groups. However, niether significant differences emerged between AN clusters only nor HC clusters only at the post-hoc level. Discussion: An underlying neuropsychological heterogeneity may exist in AN. We encourage future studies to investigate whether the identified profiles and their association with clinical characteristics are replicable. We cautiously suggest that neuropsychological profiling may have potential to both inform future research and have possible clinical benefits through individually tailored treatment strategies.